A Novel Phase of Li15Si4 Synthesized under Pressure. Issue 12 (14th April 2015) - Zeng, Zhidan; Zeng, Qingfeng; Liu, Nian; Oganov, Artem R.; Zeng, Qiaoshi; Cui, Yi; Mao, Wendy L.
<x xml:space="preserve">Abstract</x> Li15Si4, the only crystalline phase that forms during lithiation of the Si anode in lithium‐ion batteries, is found to undergo a structural transition to a new phase at 7 GPa. Despite the large unit cell of Li15Si4 (152 atoms in the unit cell), ab initio evolutionary metadynamics (using the USPEX code) successfully predicts the atomic structure of this new phase (β‐Li15Si4), which has an orthorhombic structure with an Fdd2 space group. In the new β‐Li15Si4 phase Si atoms are isolated by Li atoms analogous to the original cubic phase (α‐Li15Si4), whereas the atomic packing is more efficient owing to the higher SiLi coordination number and shorter SiLi, LiLi bonds. β‐Li15Si4 has substantially larger elastic moduli compared with α‐Li15Si4, and has a good electrical conductivity. As a result, β‐Li15Si4 has superior resistance to deformation and fracture under stress. The theoretical volume expansion of Si would decrease 25% if it transforms to β‐Li15Si4, instead of α‐Li15Si4, during lithiation. Moreover, β‐Li15Si4 can be recovered back to ambient pressure, providing opportunities to further investigate its properties and potential applications.